Submicrometre‐sized EuPO4 hollow spheres: template‐directed synthesis and luminescent properties. (6th March 2019) - Zhang, Lihui; Bai, Suzhen; You, Hongpeng; Wu, Huatao; Peng, Qinlong; Li, Weili; Cao, Kesheng; Zhou, Yanbiao
Abstract : Submicrometre‐sized EuPO4 hollow spheres were synthesised by utilising the colloidal spheres of Eu(OH)CO3 as the sacrificial template, for the first time. The EuPO4 hollow spheres were investigated by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and photoluminescence, respectively. The EuPO4 hollow spheres exhibit red colour emission from 5 D0 – 7 F J ( J = 1, 2, 3, 4) transitions of the Eu 3+ ions. The obtained EuPO4 hollow spheres may have potential applications in cell biology, drug release, diagnosis, due to the high chemistry stability and luminescence function.